GAYA KOMUNIKASI YANG EFEKTIF PADA LINGKUNGAN ORGANISASI PUBLIK - Olivia Tahalele (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Different communication styles in the organizational environment can hinder the quality of public service performance. The diversity of services that must be provided by office employees at the Faculty of Social and Political Sciences, Pattimura University from students, lecturers, education staff forms a variety of communication patterns. The research method used in this research is descriptive quantitative by distributing question sheets to students and lecturers to measure effective communication style. Research findings related to (1). employee effectiveness (Y) 0.691, (2). The organizational communication dimension (Y) is 0.721. (3). The Effectiveness of Employee Work Communication (Y) is 0.704 (70.4%). So it can be concluded that the maximum embodiment of Organizational Communication Effectiveness is at the Faculty of Social